Case Report: New‐Onset Retinal Migraine After Transseptal Catheterization. Issue 2 (30th December 2019) - Richmond, Lynn; Schneider, Ralph P.; Steffel, Jan; Sandor, Peter S.; Tarnutzer, Alexander A.
Abstract : Background: While new‐onset migraine headaches and binocular visual aura have been reported after transseptal catheterization (TSC), this case suggests that retinal aura may emerge also after this procedure. Case Description: This 38‐year‐old male with paroxysmal atrial fibrillation had received TSC and cryoablation, and subsequently developed isolated monocular aura phenomena. The first episode happened a few hours after the intervention and was not accompanied by headache or other aura phenomena. The patient's history was negative for migraine. Brain magnetic resonance imaging demonstrated 2 lacunar diffusion restrictions in the left medial cerebral artery territory that were most likely catheterization related. Over the next 14 days, 3 additional, stereotyped episodes (duration = 20‐30 minutes) with zigzag lines and flickering small bright dots in the central visual field of one eye (moving laterally) occurred. A central scotoma was noted during one episode. Conclusions: This is the first case with retinal aura phenomena meeting International Classification of Headache Disorders diagnostic criteria for retinal migraine, suggesting that this rare migraine variant can be triggered by TSC.